2020
DOI: 10.1017/s0025315420000624
|View full text |Cite
|
Sign up to set email alerts
|

Morphometric analysis of the shell of the intertidal gastropod Echinolittorina lineolata (d'Orbigny, 1840) at different latitudes along the Brazilian coast

Abstract: Morphometric analysis is one of the tools widely used to quantify, analyse and describe the variations in the biological forms of animals. In this study, we examined the linear morphometric variations of the shell of the small intertidal gastropod Echinolittorina lineolata and compared the patterns to identify variations among populations and between sexes. The individuals were collected from latitudes 3°S, 14°S, 21°S and 23°S along the Brazilian coast. Traditional morphometric analysis was performed, and the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…Thus, tropical Littorinidae may be at risk in environments subject to extreme climatic events that cause desiccation stress (Marshall et al, 2018;Brahim et al, 2018). Differences in shell morphology or size and in survival of littorinids at different latitudes were also observed by Matos et al, (2020) for Echinolittorina lineolata (d'Orbigny, 1840) and Bosso et al, (2022) for L. saxatilis (Olivi, 1792).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, tropical Littorinidae may be at risk in environments subject to extreme climatic events that cause desiccation stress (Marshall et al, 2018;Brahim et al, 2018). Differences in shell morphology or size and in survival of littorinids at different latitudes were also observed by Matos et al, (2020) for Echinolittorina lineolata (d'Orbigny, 1840) and Bosso et al, (2022) for L. saxatilis (Olivi, 1792).…”
Section: Discussionmentioning
confidence: 99%
“…Shell morphometrics approaches in gastropod molluscs are widely used because of their easy application and low cost (Chagas et al ., 2018; Barros et al ., 2020; Matos et al ., 2020). However, according to Doyle et al .…”
Section: Discussionmentioning
confidence: 99%
“…In gastropod molluscs, shell shape morphometrics is one of the most important methods for the identification of groups, in addition to establishing intraspecific variations, latitudinal variations and ecological relationships (Cruz et al ., 2012; Haumahu & Uneputty, 2018; Hamli et al ., 2020; Matos et al ., 2020). However, the study of shell shape ratios is poorly reported in the literature (Hamli et al ., 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Rochia nilotica comestibles turf algae, which have fast growth with a high turnover rate that can tolerate stress very well and the colonization of turf algae is by coral substrate and the environment of the reef (Sweirts and Vermeij 2016;Harvey et al 2021;De Carvalho and Villaça 2021). According to Matos et al (2020), the width of the shell appears larger if individuals have a larger foot, which provides higher adhesion to the substrate.…”
Section: Shell Length/heightmentioning
confidence: 99%